Some Gram-negative Lipoproteins Keep Their Surface Topology When Transplanted from One Species to Another and Deliver Foreign Polypeptides to the Bacterial Surface - Fantappiè, Laura (Mol Cell Proteomics, 2017)
In Gram-negative bacteria, outer membrane-associated lipoproteins can either face the periplasm or protrude out of the bacterial surface. The mechanisms involved in lipoprotein transport through the outer membrane are not fully elucidated. Some lipoproteins reach the surface by using species-specific transport machinery. By contrast, a still poorly characterized group of lipoproteins appears to always cross the outer membrane, even when transplanted from one organism to another. To investigate such lipoproteins, we tested the expression and compartmentalization in E. coli of three surface-exposed lipoproteins, two from Neisseria meningitidis (Nm-fHbp and NHBA) and one from Aggregatibacter actinomycetemcomitans (Aa-fHbp). We found that all three lipoproteins were lipidated and compartmentalized in the E. coli outer membrane and in outer membrane vesicles. Furthermore, fluorescent antibody cell sorting analysis, proteolytic surface shaving, and confocal microscopy revealed that all three proteins were also exposed on the surface of the outer membrane. Removal or substitution of the first four amino acids following the lipidated cysteine residue and extensive deletions of the C-terminal regions in Nm-fHbp did not prevent the protein from reaching the surface of the outer membrane. Heterologous polypeptides, fused to the C termini of Nm-fHbp and NHBA, were efficiently transported to the E. coli cell surface and compartmentalized in outer membrane vesicles, demonstrating that these lipoproteins can be exploited in biotechnological applications requiring Gram-negative bacterial surface display of foreign polypeptides.